Actualization of Religious Moderation Values for Students at State Islamic University in Indonesia - Muhammad Sholeh (International Journal of Social Science and Religion (IJSSR), 2023)
Indonesia is a pluralistic country and has much plurality. With this plural, it seems to be a "double-eyed" reality that we must be able to address correctly. On the one hand, diversity will have a positive value which will become a blessing and even a social force when we stick to the four pillars of national consensus, which contain the fundamental conception of the nation that can sustain the greatness, integrity, glory, and diversity of Indonesia. But at the same time, the existence of plurality and the reality of plurality can also have a negative value, provoking potential chaos and conflict between communities in Indonesia. Higher education is the last bastion of the nation's children in obtaining formal education, so higher education has a vital role in instilling religious moderation so that an understanding will be formed that in the context of diversity, it is necessary to uphold good values ​​to avoid intolerant, discriminatory behavior, not fanatically concerned with the interests of their group, and think extreme. Religious moderation in PTKI is to build mutual understanding from an early age between students with different religious beliefs to avoid sectarianism and be wise in acting and processing information.